NATURAL AND CLIMATIC CHARACTERIZATION OF THE REPUBLIC OF CHAD AND ANTHRAX INCIDENCE - Mahamat Nguerabe Yamtinina; Ban-Bo Bebanto Antipas (Ветеринария сегодня)
The paper addresses the effect of complex of natural and socio-economical factors on epizootic anthrax spread in the Republic of Chad as the disease remains a significant problem for livestock farming. Moreover, incidence of anthrax in humans due to exposure to diseased animals is steadily increasing. There are three climatic zones in the country territory that differ in rainfall level, relief and farming system. Regional differences in territorial dependence of anthrax nidus activity as well as its cycling and seasonal character were detected. Influence of some natural and economical factors on epizootic situation was assessed. No anthrax cases in animals were reported in Saharan natural-climatic zone for the analyzed period. Therewith, there are about 460,000 cattle in this zone and no anti-anthrax measures are taken. This fact can be accounted for desert arid climate and absence of rainfalls in this natural-climatic zone. In Sahelo and Sudan zones anthrax outbreaks in cattle are regularly reported due to higher moisture levels especially during raining season. Performed studies were aimed at improvement of measures for anthrax prevention in the Republic of Chad.